Variation in the density and body size of a threatened foundation species across multiple spatial scales. Issue 8 (18th May 2022) - Leong, Rick C.; Bugnot, Ana B.; Marzinelli, Ezequiel M.; Figueira, Will F.; Erickson, Katherine R.; Poore, Alistair G. B.; Gribben, Paul E.
Abstract : Population characteristics (e.g. density and body sizes) of foundation species can affect their own persistence and provisioning of ecosystem functions. Understanding the drivers of population characteristics of foundation species at multiple spatial scales is therefore critical for maximizing ecosystem functions of restored habitats. We analyzed variation in population characteristics (densities, 95th percentile, and median lengths of live oysters) of the Sydney rock oyster, Saccostrea glomerata, on remnant oyster reefs at regional scales (among three estuaries) along an approximately 250 km of coastline in New South Wales, Australia. We then analyzed how population characteristics were further related to spatial attributes at smaller spatial scales including within‐patches (rugosity, distance to patch‐edge, and elevation), whole‐patches (size and shape), and among‐patch (connectivity) within each estuary. The densities and body sizes of S. glomerata were related to spatial attributes occurring within‐patch (e.g. elevation), whole‐patch (e.g. shape), and landscape (i.e. connectivity) scales, but these relationships varied among estuaries. The greatest variation in oyster density and size occurred at regional scales, suggesting that processes acting at larger spatial scales (e.g. water quality and/or climate) set the context for smaller scale influences on oyster characteristics. Our results highlight the potential importance of incorporating site‐specific, spatial attributes in the design of restored oyster reefs to maximize ecosystem services and functions provided by restoration efforts.